PENETAPAN KADAR DIOSGENIN DALAM EKSTRAK AIR Costus speciosus SECARA HPLC - Hari Susanti; Subagus Wahyuono; Ratna Asmah Susidarti; Ika Puspita Sari (Majalah Obat Tradisional, 2017)
Costus speciosus has been reported to have biological activity among antidiabetic, antihyperlipidemia, antioxidants. One of the chemical constituents that is responsible for some of the biological activity is diosgenin. This study aimed to determine diosgenin content of Costus speciosus water extract (CS). Water extract of CS was obtained with infundation method. The extract was dried using freeze dryer. The assay of diosgenin was performed by HPLC method. HPLC system used: LiChrospher® 100 RP-18 endcapped (5 µm) column length 25cm, colimn id 4 mm as stationary phase, acetonitrile-water (9: 1 v/v) as mobile phase, flow rate 2mL/min and UV detection at 205 nm. HPLC method developed was linear in the range 20-200 μg mL with R = 0.9999 ; slope = 6423.7; and intercept = -4280.5; LOD = 2.14 ug/mL and LOQ = 6.50 mg/mL; and recovery 100.63 %. Diosgenin levels in CS was 0.279 %. The developed HPLC method is relatively simple, rapid, sensitive, and accurate to determine the content of diosgenin in water extracts of Costus speciosus.